Metabolomics atlas of oral 13C-glucose tolerance test in mice - Lopes, Magno; Brejchova, Kristyna; Riecan, Martin; Novakova, Michaela; Rossmeisl, Martin; Cajka, Tomas; Kuda, Ondrej (Cell reports, 2021)
Glucose tolerance represents a complex phenotype in which many tissues play important roles and interact to regulate metabolic homeostasis. Here, we perform an analysis of 13C6-glucose tissue distribution, which maps the metabolome and lipidome across 12 metabolically relevant mouse organs and plasma, with integrated 13C6-glucose-derived carbon tracing during oral glucose tolerance test (OGTT). We measure time profiles of water-soluble metabolites and lipids and integrate the global metabolite response into metabolic pathways. During the OGTT, glucose use is turned on with specific kinetics at the organ level, but fasting substrates like β-hydroxybutyrate are switched off in all organs simultaneously. Timeline profiling of 13C-labeled fatty acids and triacylglycerols across tissues suggests that brown adipose tissue may contribute to the circulating fatty acid pool at maximal plasma glucose levels. The GTTAtlas interactive web application serves as a unique resource for the exploration of whole-body glucose metabolism and time profiles of tissue and plasma metabolites during the OGTT.
Keywords: Tissue Distribution; lipidy; glucose tolerance; glukózový toleranční test; krevní glukóza; metabolomika; Metabolomics; pathway analysis; Time Factors; metabolomics atlas; myši inbrední C57BL; mužské pohlaví; metabolom; Energy Metabolism; lipidomics; metabolite cycling; Mice; 13C; Lipids; Metabolome; brown adipose tissue; energetický metabolismus; Blood Glucose; zvířata; tkáňová distribuce; Lipidomics; Tandem Mass Spectrometry; biologické markery; de novo lipogenesis; chromatografie kapalinová; časové faktory; metabolomics; myši; tandemová hmotnostní spektrometrie; Biomarkers; hmotnostní spektrometrie s elektrosprejovou ionizací; Chromatography, Liquid; tracer analysis; Glucose Tolerance Test; lipidomika; Mice, Inbred C57BL; Spectrometry, Mass, Electrospray Ionization; Male; Animals